Designing Web-Based Application for English Tenses Learning - Tatan Tawami; Retno Purwani Sari; Vincent Limountha (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
This paper aims to present the design and development of a web-based English tense learning application as a creative response to the educational challenges posed by the COVID-19 pandemic. The application focuses on enhancing the receptive and productive skills needed for English tenses, considering the preferences and needs of the e-generation. The research employs the SDLC Sommerville model for application development. It utilizes a qualitative descriptive research methodology to address various research issues, including content formulation and developing performance-based English tense materials. The article aims to contribute a valuable alternative learning method to facilitate English language learning and creative language projects, particularly those involving tenses and their uses. Key words: Design; Web-based Application; English Tenses Learning